TINJAUAN WAYANG BEBER SEBAGAI SEQUENTIAL ART - Sayid Mataram (Canthing, 2014)
Indonesia is a country with a variety of tribes that each - each of which has artifacts of art. The artifact is a manifestation of the wisdom and ancestral forms of expression. Many of these artifact is a working prototype of what is in today. One of them is Wayang Beber is one of the working prototype of sequential art